Pricing methods in outcome-based contracting: δ4: safety-based pricing. (1st November 2020) - Alkhatib, Nimer S.; Bhattacharjee, Sandipan; McBride, Ali; Ramos, Kenneth; Slack, Marion; Erstad, Brian; Abraham, Ivo
Abstract: Aims: Six Delta is a six-dimensional independent platform for outcome-based pricing/contracting. The fourth dimension (δ4) estimates prices on the basis of assessments of the safety of the drug using an ex ante analysis based on clinical trial data. We describe this dimension's methodology and present a proof-of-concept application to the treatment of non-small cell lung cancer (NSCLC) with EGFR mutation with osimertinib. Materials and methods: The safety-based pricing dimension utilizes a four-step method: 1) pooling adverse events (AE), standardizing, estimating 95%Cis, and adjusting for time; 2) estimating correction factors and corrected probabilities of AEs; 3) estimating the probability of at least one adverse event (AE) occurring and leading to treatment discontinuation; and 4) estimating ranges for payback percentages and performing Monte Carlo Simulation to estimate a DSPSafety . A proof-of-concept exercise with osimertinib in NSCLC was performed for two hypothetical outcome-based contracts: 1-year (2019–2020) and 2-year (2019–2021). We estimated the DSPSafety based on the grade 3/4 AEs observed for osimertinib and standard of care. The 2018 wholesale acquisition cost (WAC) of osimertinib at $14, 616 for a 30-day prescription was used. Results: AEs3/4 were retrieved from the FLAURA trial. In the 1-year contract, the DSPSafety of osimertinib was estimated at $14, 627 (or +0.08% the 2018 WAC) for a 30-day prescription. In the 2-year contract, the DSPSafety of osimertinib was estimated at $14, 516 (or −0.68% the 2018 WAC) for a 30-day prescription. Conclusions: We demonstrated that ex ante pricing methods-based paybacks for safety issues leading to treatment discontinuation can be integrated into our proposed Six Delta platform for outcome-based pricing/contracting.